Risk management and coping strategies climate change and agriculture in the Philippines - Roumasset, James; Ravago, Majah-Leah; Jandoc, Karl Robert L. (2016)
We provide an initial framework to guide government priorities among programs seeking to reduce the natural-disaster vulnerability of Philippine farm households. The framework sheds light on the pros and cons of alternative policies to reduce household vulnerability, paying particular attention to the role of discounting. The limited coping tools available to low-income households strengthen the case for preventive polices that reduce the probability or the severity of damages. We argue, however, that the inability of poor households to cope with increased exposure to risks does not necessarily imply that social insurance programs should be expanded. Finally, inasmuch as disaster risk management policies at the national level typically lack coherent foundations, we suggest how the farm level risk management framework might be expanded to the national level.
Keywords: Natural disasters; Disasters -- Economic aspects; Risk